THE INFLUENCE OF E-PURCHASING AND GOOD GOVERNANCE ON URBAN AND REGIONAL PLANNING QUALITY AT THE REGIONAL SECRETARIAT OF SIMALUNGUN REGENCY - Sihotang, Friska Novalitas (Mimbar Administrasi Mandiri, 2025)
This study analyzes the influence of the e-purchasing system on the fulfillment of the principles of good governance and the quality of regional and urban planning in the Simalungun Regency Regional Secretariat. Using an explanatory quantitative design with total sampling, as many as 41 employees involved in procurement and planning became respondents. Data were collected through a Likert scale questionnaire and tested with Pearson's correlation for validity as well as Cronbach's Alpha for reliability (α = 0.991). The residual normality assumption is met. Multiple linear regression analysis is used to test the partial and simultaneous influence of variables. The results show that e-purchasing has a significant effect on good governance, increasing transparency, accountability, and process efficiency. Good governance practices in procurement have been identified as having run quite well. The effect of e-purchasing on planning quality was very significant and dominant (B = 0.883; β = 0.886; t = 35.929; p < 0.001), while good governance also had a positive and significant effect (B = 0.143; t = 4.697; p < 0.001). Simultaneously, the two variables explain almost all variations in planning quality (R² = 0.999; F = 18,712,641; p < 0.001), indicates the feasibility of the model. The findings confirm that the integration of e-purchasing and good governance is an operational prerequisite for realizing effective, efficient, and accountable regional development planning. Recommendations include strengthening human resource capacity, procurement data governance, and improving infrastructure and derivative rules to maintain consistency in implementation